Innovation and New Technologies in Spine Surgery, Circa 2020: A Fifty-Year Review - Cornwall, G. Bryan; Davis, Andrea; Walsh, William R.; Mobbs, Ralph J.; Vaccaro, Alexander (Frontiers in Surgery, 2020)
Spine surgery (lumbar, cervical, deformity, and entire spine) has increased in volume and improved in outcome over the past 50 years because of innovations in surgical techniques and introduction of new technologies to improve patient care. Innovation is described as a process to add value or create change in an enterprise’s economic or social potential. This mini review will assess two of three assessments of innovation in spine surgery: scientific publications and patents issued. The review of both scientific publications and issued patents is a unique assessment. The third assessment of innovation: regulatory clearances of medical devices and equipment for spine surgery and their evolution over time, will also be discussed.